On the pattern of Salmonella serotypes in fishery products, froglegs and processing environments - Shrivastava, K.P., Gopalakrishna Iyer, T.S. and (Fishery Technology, 2021)
Thirty four different serotypes of Salmonella have been isolated from aquatic products. The number of serotypes from frozen froglegs were 22. Only four serotypes were isolated from frozen shrimps. S. weltevreden predominates in frozen shrimps and fish. S. roan and S. larochelle were isolated for the first time in India. Isolation of six rare serotypes of Salmonella has also been reported.